Immunoliposomes for Alzheimer's Disease Therapy - Joana A. Loureiro (2013)
There have been several efforts to understand the etiology of Alzheimer's disease (AD) and to find the cure for such debilitating disease. Despite the efforts, there is still no cure or effective treatment for AD. Many reasons contribute for such disappointing outcome, being one of them the fact that the transportation through the blood-brain barrier (BBB) remains an obstacle.